UJI AKTIVITAS ANTIOKSIDAN TEH HERBAL BUNGA TELANG DENGAN PERBEDAAN PEMANIS SEBAGAI ALTERNATIF PENGOBATAN HIPERTENSI - Nofitasari, Risma Septyana; Saputri, Romadhiyana Kisno; Nisak, Siti Khoirun; Basith, Abdul (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2024)
Hypertension can be caused by an imbalance between free radicals and antioxidants in the body. Consumption of sweetened herbal tea can affect antioxidant levels. This study aims to test the antioxidant activity of telang flower herbal tea as an alternative treatment for hypertension and hedonic testing of the formulated herbal tea. Telang flower herbal tea was formulated without sweetener, sugar sweetener, stevia leaf sweetener, sorbitol and cyclamate sweetener. Telang flower herbal tea was brewed with 70℃ water then phytochemical screening of flavonoids, saponins and tannins using standard methods and antioxidant activity using DPPH method. Hedonic test was conducted by assessing the liking of 20 panellists for herbal tea on a scale of 1-5. Unsweetened telang flower herbal tea, sugar sweetener, stevia leaf sweetener, sorbitol and cyclamate sweetener had values of 247.97 ppm; 178.38 ppm; 497.765 ppm; 164.87ppm; 224.96 ppm with hedonic test values of 3.25; 4.05; 3.55; 3.55; 3.35 respectively. The antioxidant activity of telang flower herbal tea with different sweeteners is in the weak to moderate category and panellists like herbal tea with sugar sweetener the most.